APLIKASI SISTEM INFORMASI GEOGRAFIS LOKASI APOTEK DI MASAMBA BERBASIS ANDROID - Emelinda Yuyun; Mukramin Mukramin; Muhlis Muhallim (CV. Denasya Smart Publisher, 2024)
The aim of this research is to design a Geographic Information System application for pharmacy locations in Masamba. Building a Geographic Information System application for pharmacy locations in Masamba. This research uses the Prototype research method. Data collection methods in this research are data documentation, observation, interviews and questionnaires. In designing the application, four diagrams from the Unified Modeling Language (UML) are used, namely Use Case Diagram, Activity Diagram, Sequence Diagram and Class Diagram. The software used to build this application is Android Studio as a design editor, XAMPP as a web server, and MySQL as a Database and Java as a programming language. The system has been tested using the black box testing method. This research produces an application that makes it easier and faster to search for pharmacies in Masamba. The feasibility of the system has been tested using the Likert Scale Method and based on the feasibility percentage value, this application is very suitable for use because it has a percentage value of 84.89%.